A comparative field efficacy trial of three treatment programs against endo- and ectoparasites in naturally infected dogs - Raw, Cameron; Traub, Rebecca J.; Wiethoelter, Anke (Frontiers in Veterinary Science, 2024)
IntroductionTropical climates in remote Aboriginal and Torres Strait Islander communities in northern Australia are conducive to the transmission of canine helminths such as hookworms, as well as ectoparasites such as fleas and ticks. In addition to their veterinary importance, these parasites may present a zoonotic risk either directly, or as potential vectors for bacterial pathogens. These factors necessitate efficacious and effective antiparasitic treatment programs for community dogs.MethodsA cluster-randomised trial was performed on three islands in the Torres Strait to examine the short-term efficacy and medium-term effectiveness of three treatment programs. Treatments administered included oral oxibendazole/praziquantel (Paragard®) and oral afoxolaner (Nexgard®); topical moxidectin/imidacloprid (Advocate®) and imidacloprid/flumethrin collars (Seresto®); and off-label oral ivermectin (Bomectin®). Canine faecal samples were collected and examined for endoparasites by faecal flotation and real-time PCR at baseline, 7–11 days after treatment and 6 months later.ResultsThe proportion of dogs positive for Ancylostoma caninum at baseline and negative at day 7–11 was 9% (95% CI 4.4–17.4) for dogs treated with oxibendazole, 56.4% (95% CI 41–70.7) for moxidectin, and 89.7% (95% CI 73.6–96.4) for ivermectin. Faecal flotation results showed a greater than 90% egg reduction in 29.2% (95% CI 19.9–40.5) of dogs treated with oxibendazole, 79.4% (95% CI 63.2–89.7) for moxidectin, and 95% (95% CI 76.4–99.1) for off-label ivermectin. Elimination of ectoparasite infestation was observed at day 7–11 in 69.9% (95% CI 56.7–80.1) of dogs treated with afoxolaner, 80% (95% CI 60.9–91.1) with imidacloprid/flumethrin collars, and 0% (95% CI 0–11.7) for off-label ivermectin. Mixed effects modelling revealed only treatment group to be significantly associated with outcome measures.DiscussionBased on these study results, the poor efficacy of oxibendazole against A. caninum renders it inept for treatment, while ivermectin and moxidectin were suitable. Ivermectin was unsuitable for ectoparasite treatment due to its poor efficacy, while afoxolaner and imidacloprid/flumethrin collars appear suitable.